An investigation of atherosclerotic markers in patients with posterior semi-circular canal benign paroxysmal positional vertigo - Baykara, Murat; Polat, Cahit; Öztürk, Cansu; Karlıdağ, Turgut (İstanbul Üniversitesi, 2014)
Objectives: This study aims to investigate the presence and incidence of arteriosclerosis in patients with benign paroxysmal positional vertigo BPPV . Patients and Methods: A total of 89 patients who were admitted to the ear, nose, throat outpatient clinic with complaint of vertigo and were diagnosed with BPPV based on the positive Dix-Hallpike test results were included BPPV group between January 2010 and July 2010. Data from otological asymptomatic controls n=129 who were referred to the radiology department from other clinics for ultrasound examination were obtained. Intima-media thickness and arteriosclerosis measurements were carried out. Arteriosclerosis measurement was performed through a Doppler ultrasound. Results: No statistically significant difference in carotid, femoral intima-media thicknesses and elastic modulus measurements between the controls and BPPV group. In the BPPV group, carotid artery cross-sectional compliance, cross-sectional distensibility, femoral artery cross-sectional compliance and cross-sectional distensibility were statistically significantly lower. Conclusion: Our study results suggest that atherosclerotic changes may play a role in the underlying etiology of BPPV.

Amaç: Bu çalışmada benign paroksismal pozisyonel vertigo BBPV olan hastalarda arteriyoskleroz varlığı ve insidansı araştırıldı.Hastalar ve Yöntemler: Ocak 2010 ve Temmuz 2010 tarihleri arasında vertigo yakınması ile kulak, burun, boğaz polikliniğine başvuran ve pozitif Dix-Hallpike test sonucuna göre BPPV tanısı konan toplam 89 hasta BPPV grubu çalışmaya alındı. Diğer kliniklerden ultrason incelemesi için radyoloji kliniğine sevk edilen otolojik asemptomatik kontrollerin verileri elde edildi. İntima-media kalınlığı ve arteriyoskleroz ölçümleri yapıldı. Arteriyoskleroz ölçümü Doppler ultrason ile yapıldı.Bulgular: Karotis, femoral intima-media kalınlığı ve elastik modülüs ölçümleri açısından kontroller ve BPPV grubu arasında istatistiksel olarak anlamlı bir fark yoktu. Karotis arter çapraz kesitsel uyum, çapraz kesitsel distansibilite, femoral arter çapraz kesitsel uyum ve çapraz kesitsel distansibilite BPPV grubunda istatistiksel anlamlı olarak daha düşüktü.Sonuç: Çalışma bulgularımız, aterosklerotik değişikliklerin BPPV’nin altta yatan etyolojisinde bir rolü olabileceğini göstermektedir
Arka yarı dairesel kanal benign paroksismal pozisyonel vertigolu hastalarda aterosklerotik belirteçlerin araştırılması